The Poetry in Philosophy Essays in Honor of Christos C. Evangeliou - Mitsis, Phillip (Parnassos Press - Fonte Aretusa, 2021)
In this wide-ranging volume, fifteen distinguished scholars come together to honor the life and scholarship of Christos C. Evangeliou. The papers examine topics he is well-known for, including the origins, character, and influence of Hellenic philosophy; its place among the other philosophies of the ancient and modern world; and its relation to religious rites, athletic contests, and daily life. Most eras of Hellenic philosophy are touched on, including the Presocratics, Plato, Aristotle, Hellenistic philosophers, Neoplatonism, and Byzantine philosophy. Topics treated range from democracy, vegetarianism, and the environment, to consciousness, moral epistemology, free will, and happiness. Philosophy in poetry and poetry in philosophy are discussed through such figures as Homer, Parmenides, Aeschylus, and Plutarch.